2021
DOI: 10.3390/cancers13050983
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemoradiotherapy Followed by Esophagectomy with Three-Field Lymph Node Dissection for Thoracic Esophageal Squamous Cell Carcinoma Patients with Clinical Stage III and with Supraclavicular Lymph Node Metastasis

Abstract: Background: Neoadjuvant chemoradiotherapy (NACRT) followed by esophagectomy is now the standard treatment for patients with resectable advanced thoracic esophageal squamous cell carcinoma (ESCC) worldwide. However, the efficacy of NACRT followed by esophagectomy with three-field lymph node dissection for clinical Stage III patients and for clinical Stage IVB patients with supraclavicular LN metastasis has not yet been determined. Methods: Between 2008 and 2018, 94 ESCC patients diagnosed as clinical Stage III … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Although individual and geographical survival rates for CRC vary, this research-based study aimed to look at the various prognostic factors that influence the survival rate of CRC patients in HUSM. This study outcome shows that the overall five-year survival rate in patients with colorectal cancer was 62.5%, which is similar to the data (60%) reported by Barnous, Somi [ 23 ] and 64.5% reported from the Surveillance, Epidemiology and End Results (SEER) Program from 2008 to 2014, as well as in the United States (64.8%) [ 24 ], Australia (63.4%) [ 25 ], including the Asian nations of China (60.1%) [ 26 ], Japan (68.4%) [ 27 ] (68.4%), South Korea (60.0%) [ 28 ], and Iran (58.5%) [ 29 ]. Given the advanced presentation of CRC in the present study among the age groups, the elderly age group (70 years and above) have the poorest survival rate (54.1%) among all the age groups, just as reported in a study in the UK, which revealed that the incidence rates of CRC in the UK are primarily diagnosed in persons aged 75 and above, the highest among 85–89-year-olds, and this groups is associated with the poorest survival prognosis [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 80%
“…Although individual and geographical survival rates for CRC vary, this research-based study aimed to look at the various prognostic factors that influence the survival rate of CRC patients in HUSM. This study outcome shows that the overall five-year survival rate in patients with colorectal cancer was 62.5%, which is similar to the data (60%) reported by Barnous, Somi [ 23 ] and 64.5% reported from the Surveillance, Epidemiology and End Results (SEER) Program from 2008 to 2014, as well as in the United States (64.8%) [ 24 ], Australia (63.4%) [ 25 ], including the Asian nations of China (60.1%) [ 26 ], Japan (68.4%) [ 27 ] (68.4%), South Korea (60.0%) [ 28 ], and Iran (58.5%) [ 29 ]. Given the advanced presentation of CRC in the present study among the age groups, the elderly age group (70 years and above) have the poorest survival rate (54.1%) among all the age groups, just as reported in a study in the UK, which revealed that the incidence rates of CRC in the UK are primarily diagnosed in persons aged 75 and above, the highest among 85–89-year-olds, and this groups is associated with the poorest survival prognosis [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 80%
“…A total of 127 consecutive patients with confirmed TESCC treated with NACRT followed by curative surgery at Akita University Hospital between 2009 and 2017 were enrolled in this retrospective cohort study. Patients with a supraclavicular lymph node (cM1 lymph node) were included [ 14 ]. Clinical staging was done according to the TNM classification of the UICC (8th edition) [ 11 ], based on esophagogastroduodenoscopy (EGD), contrast-enhanced computed tomography (CE-CT), and positron emission tomography (PET-CT).…”
Section: Methodsmentioning
confidence: 99%
“…4,5 The clinical significance of SCLN metastasis in patients with oesophageal cancer has been previously evaluated. [16][17][18][19] Sato et al 20 concluded that treating SCLN as a regional node was appropriate for patients with resectable upper and middle thoracic oesophageal SCC because they found no significant difference in 5year OS rates between patients with or without SCLN metastasis (41.3% vs. 57.6%, P = 0.39). In another multicentre study reported by Kroese et al, 21 with oesophagogastric cancer and oligometastatic disease had a median OS of 16 months and the local treatment of oligometastatic disease plus systemic therapy was associated with a long-term OS.…”
Section: Discussionmentioning
confidence: 99%
“…Whether curative treatment is possible for LTOC with SCLN metastases has not been determined. Sato et al 20 reported that patients with thoracic oesophageal cancer with SCLN metastasis who received nCRT followed by oesophagectomy with three-field lymph node dissection could achieve long-term survival, with 5-year OS rate of 41.3%. Similarly, our study showed significantly better OS with nCRT+S than with other treatments (nCRT+S group: 25 months, upfront S group: 14 months and dCRT group: 8 months, P < 0.001), and the result remained consistent after IPTW (nCRT+S group: 39 months, upfront S group: 12 months and dCRT group: 8 months, P < 0.001), indicating that strategies to intensify local treatments could offer a survival benefit for patients with SCLN metastasis.…”
Section: Discussionmentioning
confidence: 99%